สภาพบังคับของแนวนโยบายพื้นฐานแห่งรัฐตามรัฐธรรมนูญแห่งราชอาณาจักรไทย พุทธศักราช 2550 - ณัฐพล บุญชิต (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
This thesis aims to study the sanctions of the directive principles of fundamental state policies under the Constitution of the Kingdom of Thailand, B.E. 2550. These provisions have shown the various tasks of the State that the Constitution’s drafters recognize that there were benefits and appropriateness to make the guidelines for managing and solving the country’s problems in long-term. These provisions were originally introduced in the Constitution of the Weimar (Federal Republic of Germany). The Weimar Constitution is thus a model for other countries on this issue, including Thailand, to adopt the provisions of the directive principles of state policies in their own Constitutions. At present, the Constitution of the Kingdom of Thailand, B.E. 2550 provides these provisions as "the Directive Principles of Fundamental State Policies." The study found that former Constitutions did not focus on the directive principles of state policies. The present Constitution’s drafters thus tried to find mechanisms or measures to apply for state policy. The Constitution of the Kingdom of Thailand, B.E. 2550 stipulated that in making legislations and making policies, the State must follow the guidelines provided by the directive principles of fundamental state policies. In addition, this Constitution determined mechanism to support the implementation of the directive principles of fundamental state policies to be more effective than the past. However, although there is an attempt to make the directive principles of fundamental state policies binding the State even more, the Constitution of the Kingdom of Thailand, B.E. 2550 does not have any clear provision about the sanctions (especially legal sanction) in case of the State does not perform or perform inconsistently with the directive principles of fundamental state policies. Therefore, these provisions should be improved by stating clear sanctions in order that they have been implemented literally according to the spirit of the Constitution.